Nephroprotective effects of Datura metel extract in gentamicin induced mice model: biochemical and histological evidences - Alam, Waqas; Khan, Haroon; Khan, Sajjad Ali; Ali, Niaz; Sharif, Naveed; Ghafar, Rukhsana; Daglia, Maria; Nazir, Sana (Cellular and Molecular Biology, 2020)
Datura metel is traditionally used as a remedy for renal toxicity. However, the nephroprotection has not been scientifically validated yet. To evaluate the nephroprotective like effect of methanolic extract of D. metel in gentamicin induced mice model, mice of either sex were divided into groups. One group received normal saline as negative control. The 2nd group received gentamicin 100mg/kg for 8 days as positive control, 3rd group received 50mg/kg silymarin as standard, while the reaming groups received 100, 200 and 300 mg/kg of MEDM and gentamicin 100mg/kg, for 8 days. The blood and urine samples were collected on 9th day, animals were then dissected and whole kidneys were removed and preserved in formalin for later histological examinations. The level of serum creatinine, blood urea nitrogen, urine creatinine and urine urea were significantly (P<0.05) elevated and the renal MDA level was also elevated significantly (P<0.05) by gentamicin in mice. After the treatment of test animals with MEDM, the elevated level of serum and urine biomarkers by gentamicin were reversed by MEDM. The nephroprotective effect was found in dose dependent manner. As the MEDM significantly protected the nephrotoxicity via its antioxidant effect. The findings of our study thus proved the scientific background for the nephroprotective effect of MEDM.